Hydrogel Encapsulation: Taking the Therapy of Mesenchymal Stem Cells and Their Derived Secretome to the Next Level - Huang, Yuling; Li, Xin; Yang, Lina (Frontiers in Bioengineering and Biotechnology, 2022)
Biomaterials have long been the focus of research and hydrogels are representatives thereof. Hydrogels have attracted much attention in the medical sciences, especially as a candidate drug-carrier. Mesenchymal stem cells (MSC) and MSC-derived secretome are a promising therapeutic method, owing to the intrinsic therapeutic properties thereof. The low cell retention and poor survival rate of MSCs make further research difficult, which is a problem that hydrogel encapsulation largely solved. In this review, safety and feasibility of hydrogel-encapsulated MSCs, the improvement of the survival, retention, and targeting, and the enhancement of their therapeutic effect by hydrogels were studied. The status of the hydrogel-encapsulated MSC secretome was also discussed.